Cytoplasmic TDP43 Binds microRNAs: New Disease Targets in Amyotrophic Lateral Sclerosis - Paez-Colasante, Ximena; Figueroa-Romero, Claudia; Rumora, Amy E.; Hur, Junguk; Mendelson, Faye E.; Hayes, John M.; Backus, Carey; Taubman, Ghislaine F.; Heinicke, Laurie; Walter, Nils G.; Barmada, Sami J.; Sakowski, Stacey A.; et al. (Frontiers in Cellular Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a progressive, fatal, and incurable neurodegenerative disease. Recent studies suggest that dysregulation of gene expression by microRNAs (miRNAs) may play an important role in ALS pathogenesis. The reversible nature of this dysregulation makes miRNAs attractive pharmacological targets and a potential therapeutic avenue. Under physiological conditions, miRNA biogenesis, which begins in the nucleus and includes further maturation in the cytoplasm, involves trans-activation response element DNA/RNA-binding protein of 43 kDa (TDP43). However, TDP43 mutations or stress trigger cytoplasmic TDP43 inclusion formation, a hallmark of postmortem ALS brain and spinal cord tissue, that may lead to aberrant protein/miRNA interactions in the cytoplasm. Herein, we demonstrated that TDP43 exhibits differential binding affinity for select miRNAs, which prompted us to profile miRNAs that preferentially bind cytoplasmic TDP43. Using cellular models expressing TDP43 variants and miRNA profiling analyses, we identified differential levels of 65 cytoplasmic TDP43-associated miRNAs, of which approximately 30% were altered by more than 3-fold. These hits included both novel miRNAs and miRNAs previously associated with ALS that potentially regulate several predicted genes and pathways that may be important for pathogenesis. Accordingly, these findings highlight specific miRNAs that may shed light on relevant disease pathways and could represent potential biomarkers and reversible treatment targets for ALS.